2004
DOI: 10.1038/sj.bjc.6602261
|View full text |Cite
|
Sign up to set email alerts
|

Expression analysis onto microarrays of randomly selected cDNA clones highlights HOXB13 as a marker of human prostate cancer

Abstract: In a strategy aimed at identifying novel markers of human prostate cancer, we performed expression analysis using microarrays of clones randomly selected from a cDNA library prepared from the LNCaP prostate cancer cell line. Comparisons of expression profiles in primary human prostate cancer, adjacent normal prostate tissue, and a selection of other (nonprostate) normal human tissues, led to the identification of a set of clones that were judged as the best candidate markers of normal and/or malignant prostate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

5
84
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 87 publications
(89 citation statements)
references
References 39 publications
5
84
0
Order By: Relevance
“…The implication of the HOXB13 gene product in different types of cancer is beginning to be elucidated. It has been proposed as a marker for prostate cancer [18], and is also believed to be involved in endometrial cancer [19], cervical cancer [20], as well as renal cell carcinoma [21], and colorectal cancer [22]. In human cutaneous malignant melanoma with distant metastasis, the expression level of certain HOX genes, including HOXB13, was higher than in those melanoma patients without metastases [23], and in endometrial cancer cells, antisense-transfection of the HOXB13 gene reduced the invasive ability of the cells [19].…”
Section: Discussionmentioning
confidence: 99%
“…The implication of the HOXB13 gene product in different types of cancer is beginning to be elucidated. It has been proposed as a marker for prostate cancer [18], and is also believed to be involved in endometrial cancer [19], cervical cancer [20], as well as renal cell carcinoma [21], and colorectal cancer [22]. In human cutaneous malignant melanoma with distant metastasis, the expression level of certain HOX genes, including HOXB13, was higher than in those melanoma patients without metastases [23], and in endometrial cancer cells, antisense-transfection of the HOXB13 gene reduced the invasive ability of the cells [19].…”
Section: Discussionmentioning
confidence: 99%
“…Foxa1 and Hoxb13 are expressed highest in the ventral lobes, at a lower level in the dorsal and lateral lobes, and weakest in the anterior lobes (9,10,29,43). During prostate carcinogenesis in the human and mouse, studies suggest that expression of both genes is maintained (31,44,45). In the homozygous knockout of either Hoxb13 or Foxa1, defects are observed in luminal cell differentiation and secretory function, with a loss of some of the same major secretory products (6,30).…”
Section: Discussionmentioning
confidence: 99%
“…In this study, we demonstrated that downregulation of HOXB13 is a common event during the colorectal tumorigenic process. Edwards et al (2005) have recently shown that HOXB13 was markedly downregulated in tumour compared to normal colon in their cDNA microarray experiment despite limited number of tumour samples. We limited patient tumour samples to those from the descending colon to rectum since the expression of HOXB13 is known to be restricted to the distal colon and rectum by both mouse and human studies (Sreenath et al, 1999;Jung et al, 2004b).…”
Section: Discussionmentioning
confidence: 99%
“…In the adult mouse, Hoxb13 is confined to the epithelial cells of the prostate and distal colon and rectum (Zeltser et al, 1996;Sreenath et al, 1999). Tissue-specific expression of HOXB13 is also well reported in human (Aarnisalo et al, 1998;Edwards et al, 2005;Hood et al, 2004;Jung et al, 2004b;Takahashi et al, 2004). The loss-of-function Hoxb13 mouse manifests inhibition of proliferation and activation of programmed cell death in the secondary neural tube and caudal somites (Economides et al, 2003).…”
mentioning
confidence: 99%